Living with breast cancer : the illness experiences of young Malay women - Szariannie binti Sulaiman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study focuses on breast cancer patients among young Malay women in several areas in Selangor and the Klang Valley. The poor prognosis and low survival rates among Malay breast cancer patients have posed many challenges not only to health practitioners but also to caregivers in making sense of and managing their illness experiences. In relation to this, thirteen breast cancer patients between the ages of 29 and 48 years old were selected for this study. The objectives of this study are to explore the illness experiences of young Malay female breast cancer patients, to analyse the influences of socio-cultural backgrounds on their illness experiences and to identify the factors that determine the choice of their treatment options. Fieldwork was carried out for 10 months from December 2013 until October 2014. The study employed a qualitative approach using participant observation, health-diary method, in-depth interviews, telephone and online interviews as well as library search. The findings of this study highlight several issues such as the perception of health and illness, breast cancer etiologies, the utilisation pattern of health services and decision making for treatment options after diagnosis. It is evident in this study that informants had associated the concept of health with strong belief in qada' and qadar of Allah, having strong semangat, maintaining harmonious interpersonal relationship with others and elements of boleh makan, boleh pergi kerja and tidak ada semput. Many of them refer to the illness as lemah semangat, tidak boleh makan, tidak boleh pergi kerja and having semput. In terms of etiology, informants categorised breast cancer illness into two categories, namely the supernatural and non-supernatural etiologies. The supernatural etiologies involve saka (guardian spirit) and spirit attacks while non-supernatural etiologies entail lifestyle, food, unhealthy working environment and hormone imbalance. As for utilisation of health services, this study has found that informants exhibited pluralistic attitudes toward seeking a cure for their illnesses. Most informants strongly believe that breast cancer illness is a chronic-type of illness, thus relying on single medication is inadequate in treating it. In relation to this, a combination of multiple treatments is often seen as a cure. With regards to decision making, it is evident that family support has a great influence on informants compliance or non-compliance to their treatment options. In addition, non-family support involving the government and non-governmental institutions, networking of friends, and breast cancer survivors provide another important mechanism for them to comply with their treatment options. They strongly believe that by complying with the suggestions given, they could treat and cure their illness. Finally, this study holds an important implication in contributing to the existing corpus of knowledge as far as medical anthropology is concerned. It is also significant for policy development in managing cancer in any multi-ethnic society.